Neural changes in Alzheimer's disease from circuit to molecule: Perspective of optogenetics. (August 2017) - Yang, Qinghu; Song, Da; Qing, Hong
Highlights: Optogenetics can alleviate and reverse the deficits of neural circuits and memory process in AD. It will be possible to find and regulate synaptic functions and related signaling molecules in AD via optogenetics. Optogenetics improves the grade of accurate analysis in molecular and circuit pathway. Targeting the molecule which is recruited in neuron circuit is a new treatment strategy for AD. Abstract: Alzheimer's disease (AD), as a crucial neurodegenerative disorder, affects neural activities at many levels. Synaptic plasticity and neural circuits are most susceptible in AD, but the detailed mechanism is unclear. Optogenetic tools provide unprecedented spatio-temporal specificity to stimulate specific neural circuits or synaptic molecules to reveal the precise function of normal brain and mechanism of deficits in AD models. Furthermore, using optogenetics to stimulate neurons can rescue learning and memory loss caused by AD. It also has possibility to use light to control the Neurotransmitter receptors and their downstream signal pathway. These technical methods have broad therapeutic application prospect.